THE ABILITY OF THE STUDENTS IN SPEAKING ABILITY BY USING DEBATE AT GRADE TWELVETH IN SMA KAMPUS NOMMENSEN PEMATANGSIANTAR - Pangaribuan, Marnala; Siahaan, Desta Gloria (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2022)
This research attempted to know the extent of the ability of students in speaking skill by using debate at grade twelveth in SMA Kampus Nommensen Pematangsiantar. This study follows methodology in qualitative since qualitative research, is concerned with qualitative phenomenon. The data to be collected in this research is the data recorded debate and the topic is “Tehnological trens in Teaching and Learning”. The writers analyzed seven (7) items of Levels of Performance Test from the students’ debate, they are: motion, themeline, timekeeper, argument, rebuttal, definition, and sum up or closing. After analyzing the data, the writers found that speaking skill at grade twelveth in SMA Kampus Nommensen Pematangsiantar by using debate test performance is not good yet, based on the result of research, the writers concluded that speaking skill by using Debate very helpful in developing speaking students including by using debate. At last, the writers suggested for the english teacher to give the students a lot of opportunity to practice speaking and have active involvement in debate and create enjoyable, fun and interesting situation as possible as the teacher can.